Targeting TGFβR2‐mutant tumors exposes vulnerabilities to stromal TGFβ blockade in pancreatic cancer - Huocong Huang; Yuqing Zhang; Valerie Gallegos; Noah Sorrelle; Mohamed Medhat Zaid; Jason Toombs; Wenting Du; Steven Wright; Moriah Hagopian; Zhaoning Wang; Abdel Nasser Hosein; Adwait Amod Sathe; et al. (EMBO Molecular Medicine)
Abstract TGFβ is important during pancreatic ductal adenocarcinoma (PDA) progression. Canonical TGFβ signaling suppresses epithelial pancreatic cancer cell proliferation; as a result, inhibiting TGFβ has not been successful in PDA. In contrast, we demonstrate that inhibition of stromal TGFβR2 reduces IL‐6 production from cancer‐associated fibroblasts, resulting in a reduction of STAT3 activation in tumor cells and reversion of the immunosuppressive landscape. Up to 7% of human PDA have tumor cell‐specific deficiency in canonical TGFβ signaling via loss of TGFβR2. We demonstrate that in PDA that harbors epithelial loss of TGFβR2, inhibition of TGFβ signaling is selective for stromal cells and results in a therapeutic benefit. Our study highlights the potential benefit of TGFβ blockade in PDA and the importance of stratifying PDA patients who might benefit from such therapy.